Patterns of inter-populational and inter-individual variation in tolerance of sublethal progressive hypoxia and warming in the European seabass Dicentrarchus labrax - Julie J. H. Nati; Charles Rodde; Charles Rodde; Charles Rodde; Felipe R. Blasco; Felipe R. Blasco; Germain Salou; Alain Vergnet; Hugues de Verdal; Hugues de Verdal; Marc Vandeputte; François Allal; et al. (Frontiers in Fish Science)
We compared tolerance of acute progressive hypoxia and warming in the three recognized populations of European seabass, Atlantic (AT), West Mediterranean (WM) and East Mediterranean (EM), that have evolved within a North-West to South-East thermal gradient, from AT to EM. We reared progeny of captive broodstock in common garden at two temperatures, 18 and 24°C, representing summer temperatures in Atlantic and East Mediterranean, respectively. At about 1 year of age, hypoxia tolerance was evaluated with static respirometry, as critical saturation for regulation of standard metabolic rate (Scrit) and regulation index (RI); while warming tolerance was evaluated by swimming respirometry, as critical thermal maximum for aerobic swimming (CTSmax). We expected AT fish systematically to be least tolerant and EM most, with WM intermediate. At 18°C, the tolerance traits were similar among populations, but they responded differently when reared at 24°C. In AT and WM, Scrit increased—tolerance declined—from 18 to 24°C, whereas in EM it did not change. In AT and WM, RI did not change from 18 to 24°C whereas in EM it increased—tolerance increased, and EM had higher RI than WM at 24°C. In AT and EM, CTSmax was similar at 18 and 24°C whereas in WM it increased—tolerance increased, and WM had higher CTSmax than AT and EM at 24°C. Therefore, the EM population is able to avoid negative effects of warmer water on hypoxia tolerance, compared to AT and WM, but this was not related to improved thermal tolerance at the warmer temperature, where WM performed better than AT and EM. Consequently, the seabass exhibits inter-populational variation in tolerance of the stressors but patterns are complex and not consistent between hypoxia and warming. We explored some potential patterns of inter-individual variation in tolerance. We found no evidence that individuals relatively tolerant of hypoxia (low Scrit, high RI) were also relatively tolerant of warming (high CTSmax). There was evidence of complex relationships with body mass, whereby tolerance of warming declined with increasing mass at 18°C but tolerance of hypoxia increased with mass at 24°C. Finally, the traits of tolerance were not dependent on individual standard metabolic rate at either temperature.